Geschiedenis van de twee watermolens en van de houten korenwindmolen van de abdij van Ninove te Ninove - Souffreau, Georges Léon (Georges L. Souffreau, 2018)
Keywords: ninove

Geschreven bronnen over de bouw van de eerste Ninoofse abdijkerk - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

Het kaartenarchief van de Ninoofse abdij herbekeken - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

Ninove, een Vlaamse premonstratenzer abdij op de grens van Brabant en op het breukvlak van stad en plateland - Vande Winkel, Georges (De premonstratenzer Abdijkerk van Ninove. Barokke pracht in luister hersteld, 2016)
Keywords: ninove

De datering van de regeerperiodes van de Ninoofse abten tot 1578 - Van De Perre, Dirk (Analecta Praemonstratensia, 2010)
Keywords: ninove

De herberg van de abdij van Ninove te Dendermonde - Van De Perre, Dirk (Gedenkschriften Oudheidskundige Kring der Stad en des Voormaligen Lands van Dendermonde, 2010)
Keywords: ninove

Inventaris van het archief van de Sint-Cornelius- en Sint-Cyprianusabdij te Ninove (met inbegrip van archieven van het Leenhof ten Berge in Woubrechtegem en de Laathoven van de abdij in Ninove en Kattem) 1092-1796 (1812) ; Rijksarchief te Beveren. Archief van de abdij van Ninove - Put, Eddy; Peersman, Catharina (Inventarissen, 2008)
Keywords: ninove

Het necrologium van de Sint-Cornelius- en Sint-Cyprianusabdij van Ninove. Tekstuitgave van de oudste twee necrologia (1185/1188-1651 en 1652-1694) met inleiding en annotaties - Van De Perre, Dirk (Analecta Praemonstratensia, 2008)
Keywords: ninove

De opkomst can de volkstalen in de oorkonden van de abdij van Ninove. Casestudy van een bewogen eeuw (1250-1350) - Peersman, Catharina (Handelingen van de Koninklijke Zuidnederlandse Maatschappij voor Taal- en Letterkunde, 2007)
Keywords: ninove

Het kapittelboek van de Ninoofse abdij (1185-1652) - Van De Perre, Dirk (Analecta Praemonstratensia, 2007)
Keywords: ninove

Over molens in Pollare en laten in Outer. Zes onuitgegeven oorkonden van de Sint-Cornelius- en Sint-Cyprianusabdij te Ninove (1215-1265). - Cock, Marcel; Van de Perre, Dirk (Het land van Aalst, 2002)
Keywords: ninove

Het Mirakelboek en de Stichtingsgeschiedenis van de Ninoofse Abdij - Bijsterveld, Arnoud-Jan A.; Van De Perre, Dirk (Universitaire Pers Leuven, 2001)
Keywords: ninove

De oudste bisschoppelijke en grafelijke oorkonden van de abdij van Ninove (1138-1167) - Van De Perre, Dirk (Analecta Praemonstratensia, 2001)
Six of the seven charters discussed above deal with the protracted conflict between the Ninove Abbey and Gerard II of Grimbergen, situated between 1144 and 1167. We consider the first (1138) of the three charters of Bishop Nicholas I of Cambrai as the authentic charter of foundation of the abbey, containing the deed of donation of Gerard I of Ninove. The second charter of 1139 is of doubtful authenticity. The episcopal charter of 1165, which contains a detailed list of goods of the abbey, is regarded as authentic. The two last mentioned charters can already be situated within the conflict between the abbey and Gerard II of Grimbergen. The abbey used the falsified charter of 1139, presumably made between 1144 and 1147, in order to avoid the conflict. With the charter of 1165 the abbey wanted – via the authority of bishop Nicholas II– to resolve the conflict once and for all. The three charters of the Counts of Flanders were issued in a very short span (between 1166-1167) at the height of the conflict. They deal with the Ninove Abbey's right of the advocatia, which was originally by hereditary right connected to the dominium of the Lords of Ninove. In his charter of 1163/1166 Count Philip of Alsace claimed this right. The 1142 charter of his father Thierry, in which Gerard I of Ninove donates the advocatia to the Count, has been drawn and issued but in 1166-1167 in the Ninove Abbey. This is a logical link between Count Philip's two charters concerning the advocatia. In the 1167 charter of the Count the conflict is definitely resolved: Gerard II of Grimbergen is forced to accept the Count's prerogatives concerning the advocatia of the abbey. At the same time we have drawn a picture of the broader context of the Count's appearance and we have proved that Philip of Alsace – with his intervention in the Ninove conflict – introduced a new kind of politics in relation to the organisation of the central authority of the Count in the county of Flanders in general and in the Land of Aalst in particular. The charters issued in the period between 1165 and 1167 were a key moment and turning point in the history of the Ninove Abbey of the 12th century. In 1167 a period of conflicts with the relatives of the founder had been ended and a new period of rest, welfare and protection by the Count had been announced. The Ninove Liber Miraculorum offers a probing report on this change.
Keywords: ninove

De relatie tussen vier dertiende-eeuwse kroniek-teksten uit de Ninoofse abdij - Van De Perre, Dirk (Het Land van Aalst, 2001)
Keywords: ninove

De voeding in de Sint-Corneliusabdij te Ninove en het Onze-Lieve-Vrouwehospitaal te Oudenaarde in de 15e eeuw - Bruynbroeck, V. (University of Gent, 1996)
Keywords: ninove

De abdijen van Ninove en Jette (Dielegem) en hun geschil over de kerk en het kapittel van Liedekerke (1092-1180) - Van De Perre, Dirk (Analecta Praemonstratensia, 1995)
Keywords: dieleghem; liedekerke; ninove

De geschiedenis van Denderwindeke. 3: Parochie en kerkelijk grondbezit tijdens de middeleeuwen inzonderheid de aanwezigheid van de abdijen van Vermand (Fr.), Vicoigne (Fr.) en Ninove (1138-1490) - Van De Perre, Dirk; Hauwe, Rik van (Het land van Aalst, 1994)
Keywords: denderwindeke; ninove; vermand; vicoigne

Een opgraving heropgegraven: Norbertijnen in Ninove, prov. Oost-Vlaanderen: interimverslag - Wouters, Werner; Peersmann, Jaak (Archeologie in Vlaanderen, 1993)
Keywords: ninove

Het altaar van Huizingen en de abdijen van Vermand, Terkameren, Ninove en Vicoigne - Van De Perre, Dirk (Analecta Praemonstratensia, 1992)
Keywords: ninove; vermand; vicoigne

Diplomatisch-paleografisch onderzoek van de oudste oorkonden van de Sint-Cornelius- en Cyprianusabdij van Ninove (1137-1300) - Van den Noortgate, Machteld (University of Gent, 1990)
Keywords: ninove

De Onze-Lieve-Vrouwkerk te Ninove - Dhanens, Elisabeth (Inventaris van het kunstpatrimonium van Oost-Vlaanderen, 1980)
Keywords: ninove

Norbertijnerabdij St. Cornelius en Cyprianus te Ninove - Coppens, Cyprianus (Analecta Praemonstratensia, 1971)
Keywords: ninove

De hoven van Sint-Corneliusabdij te Ninove - Soens, Ernest; Walters, Jozef F.A. (Luysterman-Haelterman, 1939)
Keywords: ninove

De tienden van de abdij Ninove te Melx - Soens, Ernest (Eigen schoon en de Brabander, 1935)
Keywords: ninove

Het domein der premonstratenzer abdij van Ninove - Soens, Ernest (Analecta Praemonstratensia, 1928)
Keywords: ninove

Het domein der premonstratenzer abdij van Ninove (einde) - Soens, Ernest (Analecta Praemonstratensia, 1928)
Keywords: ninove

Bladen uit de geschiedenis van Ninove - Plas, Leo (Boekhandel van Weduwe Jacobs en Zonen, 1890)
Keywords: ninove